Community Participation and Sustainability of Water Flow Project in Rwanda: A Case of Water and Sanitation Corporation in Bugesera District - Kantengwa, Monique; Kamande, Mercyline (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The communities don’t get the opportunity of fully participating in their projects which is at the core cause of the failure and unsustainability of the most of the project conducted among communities. Thus, the researcher conducted a study to evaluate the role of community participation in sustainability of water flow project in Bugesera of Rwanda. This study used 268 respondents as the primary informants of this study but before actual time of data collection the researcher used 12 respondents to measure validity and reliability of the instrument and it found that CVI is above 0.7 of content validity index. Descriptive research design was used to collect data during actual time of data collection that was presented in a table of frequency, correlation and regression to facilitate the data interpretation process. The findings of the study have revealed that there is a relationship between community participation and water flow project as proven by relationship between joint consultation and stakeholder ownership (r=0.860 and sig=0.00), between joint consultation and effective management (r=0.806 and sig=0.00), between community empowerment and stakeholder satisfaction (r=0.867 and sig=0.00) basing on the calculated p-values which are strong and positive and the calculated level of significance which is under 0.01 results indicate a positive and significant relationship between community participation and water flow project sustainability in WASAC in Bugesera District. The regression analysis results have shown the positive regression coefficients while the calculate significance levels are under 0.05 level of significance implying that community participation and stakeholder ownership is positive and significant. Hence, basing on the research findings, the researcher would like to recommend to the management to formulate policies that favor water flow project. Therefore, the researcher would like to recommend to the government to empower its communities and the community members so that the water flow project would be more sustainable. In conclusion, the findings of the study have proven a positively significant relationship between community participation and water flow project sustainability in Bugesera District, Rwanda.